The Existence of Bissu in Bugis Culture in the Contemporary Era - Indra, Andi Batara; Darussalam, Fajrul Ilmy; Aulia, Sabita; Andi Karman, Andi Karman; Jumriani, Jumriani (LP2M IAIN Palopo, 2024)
This research aims to determine the form of existence and how to maintain the existence of Bissu in Bugis culture in the Contemporary Era. This research is a qualitative type with a case study research design. Data sources are the results of interviews and literature studies. The research results show that Bissu in Bugis culture in the contemporary era still has an existence which is manifested in the form of Bissu involvement in the cultural realm. Bissu often receives invitations to activities such as commemorating the anniversaries of various regions in South Sulawesi. Besides that, another way to maintain the existence of the Bissu community in Bone Regency is by holding meetings with fellow Bissu members in South Sulawesi. Meanwhile, another way that the Bissu community maintains its existence in the contemporary era is by carrying out various activities in the community, including being a bridal make-up artist, cooking, performing rituals or performances when moving house and circumcision. Also, the Bissu community in Bone Regency also carries out open member recruitment. From the various existences and ways Bissu maintains the existence community in Bone Regency, the Bissu community is also challenged in Bugis culture in the contemporary era with the clash between religious values and cultural rituals carried out by Bissu and as LGBT issues directed at Bissu.